Contexts proposed by teachers in Papua for developing mathematics hots assessment instruments: A phenomenological study - Ismail, Raoda; Retnawati, Heri; Sugiman; Arovah, Novita Intan; Imawan, Okky Riswandha (Journal of Education and e-Learning Research, 2024)
The success of a school centers on teachers’ ability to create well-aligned educational tools. The Merdeka Belajar curriculum requires adapting assessments, including Higher-Order Thinking Skills (HOTS) questions for real-world problem-solving scenarios. This study explored contexts proposed by teachers in Papua for developing Mathematics HOTS questions. A phenomenological approach within a qualitative framework was employed involving 24 mathematics teachers from public and private schools in focus group discussions. Participants included twenty teachers from Papua, two from Central Indonesia and two from Western Indonesia. Additionally, five teachers from Papua participated in in-depth interviews. Data was analyzed using Creswell’s model with Atlas.ti software. Teachers developed HOTS assessment instruments based on daily life, scientific and social contexts. However, no cultural contexts were incorporated into these instruments by the interviewed teachers. This study highlights the importance of teacher preparedness in aligning contextual learning with the Merdeka Belajar curriculum and reveals a significant gap in using cultural contexts for HOTS assessments among teachers in Papua. These insights contribute to the discourse on math education in Indonesia advocating for the integration of cultural elements into the freedom to learn initiative.